Development of E-Module Flipbook on Science Learning to Support Sustainable Development Goals (SDGs) for Elementary School Students - Aji, Sudi Dul; Yasa, Arnelia Dwi; Dewi, Paulia Kurnia; Kumala, Farida Nur; Putri, Amelia Nurdevianti (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2022)
One of the Sustainable Development Goals (SDGs) goals is to improve the quality of learning. However, school teachers have not integrated the SDGs into the learning process. Therefore, applying the SDGs in school learning is important for students to understand global issues and overcome everyday challenges. This research aims to develop a flipbook-based science e-module that is feasible for achieving the Sustainable Development Goals (SDGs) for elementary school students that is valid and practical. This type of research is development research by adopting the Brog and Gall model. The data collection technique used is quantitative and qualitative data analysis. The subjects of this research were grade VI students at SD Negeri 3 Bandungrejosari Malang City. The instruments used in this study were interview and questionnaire instruments. The material expert validation assessment results obtained a score of 87.9% in the "very feasible" category. The average assessment of language experts shows a percentage of 94.6%, which is classified as "very feasible." Media experts also assessed the science e-module with a "very feasible" category with a feasibility level of 97.1%. The teacher's practicality questionnaire showed an average percentage of 86% with the category "Practical." Furthermore, based on the assessment of ten students after the science e-module trial, the average practicality reached 96.8% with the category "very practical." This research can be a reference for other researchers in developing SDGs-based science e-modules. So, it can be concluded that developing flipbook-based science e-modules to achieve the Sustainable Development Goals (SDGs) for elementary school students is feasible and can be used in the learning process.